The cascade of care for hepatitis B - any lessons from the HIV field? - Soriano, Vicente; Moreno-Torres, Víctor; Barreiro, Pablo; Álvarez, Carmen; Corral, Octavio; de Mendoza, Carmen (Expert Review of Anti-infective Therapy, 2026)
Introduction: HIV and hepatitis B continue to be global public health challenges. Each virus causes 1.2 million new infections annually. By 2025, roughly 40 million people live with HIV, and over 250 million have chronic hepatitis B. Areas covered: Using PubMed, we analyzed approaches to control HIV and HBV epidemics. Whereas no vaccine exists to prevent HIV acquisition, successful protective HBV vaccines are available. The high incidence of HBV is largely explained by low immunization coverage and poor HBV screening. Linkage to care and sustained provision of antivirals remain suboptimal for HBV. New potent antiviral drugs and combinations are being developed. Long-acting formulations have shown clinical efficacy in HIV but remain untested for HBV. Expert opinion: The WHO has called for eliminating both HIV and HBV as public health threats by 2030. Whereas the cascade of care for HIV is well rolled out at 80-80-80%s (diagnosed- treated-suppressed), rates are significantly lower for chronic hepatitis B (13-3-?), with only 7 million people treated. Major gaps exist at different stages of the hepatitis B cascade. There is a need to expand HBV vaccination and screening, as well as improve linkage to care and monitoring. Antiviral treatment should be provided earlier.
Keywords: chronic hepatitis B; cirrhosis; hepatitis delta; immunosuppression; liver cancer; occult hepatitis B; pre-exposure prophylaxis; reactivation; tenofovir; transmission; vaccine